Методическое обеспечение программы формирования коммуникативно-управленческой компетентности студентов педвуза - Сеитова, Р.С. (My University, 2013)
The development of communicative and managerial competence of future teachers as asubsystem of professional training of future teachers includes interconnected subsystems: content-organizational, motivational and regulatory, process-forming, and diagnostic and corrective.